The Effect of Using a Virtual Laboratory on Students' Motivation and Learning Outcomes in Physics Learning - Bahtiar Bahtiar; Azmar Azmar (Jurnal Pendidikan Fisika, 2022)
The use of virtual laboratories in the physics learning process can bridge abstract material into concrete. This study aims to analyze the differences in motivation and learning outcomes of physics taught with and without using a virtual laboratory. This type of research uses a quasi-experimental with static group comparison design. The subjects of this study were physics students in the third semester at Tadris Physics study program, UIN Mataram. The results obtained for the learning motivation variable by comparing the values of t-count and t-table are t-count (3.03) t-table (2.03). It means that there is a significant difference in learning motivation between students taught with and without virtual laboratories. Furthermore, the results obtained for the learning outcomes variable by comparing the values of t-value and t-table are t-value (4.90) t-table (2.03). This means that there is a significant difference in learning outcomes between students taught with and without virtual laboratories. So, it can be concluded that the use of virtual laboratories has an effect on students' motivation and learning outcomes in physics.